Pengaruh Pemberian Probiotik Terhadap Dinamika Kualitas Perairan Pada Beberapa Tambak Udang Vanname (Litopenaeus vannamei) Sistem Intensif - Ridhaya, Ridhaya; Febri, Suri Purnama; Komariyah, Siti; Haser, Teuku Fadlon; Insani, Sri Ayu (Fakultas Pertanian Universitas Samudra, 2024)
This research aims to analyze and determine the effect of providing probiotics on the dynamics of water quality in several intensive system vannamei shrimp ponds. The research method uses a survey method, namely taking samples directly in the field. The results of the research obtained optimal water quality parameters for the survival of vannamei shrimp in ponds A and B, namely salinity, temperature, depth, brightness, DO, pH, alkalinity, nitrite, nitrate and total hardness, while in pond C the optimal parameters were salinity, temperature, depth, brightness, DO, pH, alkalinity and total hardness. The best water quality for the growth of vannamei shrimp is found in pond A, because with a stocking density of 168 thousand fish and giving probiotics twice a week, it can produce good water quality compared to ponds B and C with probiotics given three times a week, so it can benefit farmers because of reduced use probiotics. The results of observations of phytoplankton in ponds A, B and C obtained the species Chatoceros, Dinobryon, Lauderia, Lingulodinium, Nodularia, Oscillatoria, Planktothrix, Proboscia. Meanwhile, zooplankton in ponds A, B, C were obtained by Acartia, Amphipleura pellucida, Boeckella triarticulata, Nematodes genus.